Effects of production on reproductive traits in Kansas Holstein herds - Edward P. Call (Kansas Agricultural Experiment Station Research Reports, 1988)
The analysis of dairy herds to evaluate the reported negative effect of production on reproduction failed to identify a real relationship. Higher-producing herds excel in all areas of reproductive performance, except conception rate. Of greatest importance is the annual reproductive loss that is affected by the reproductive traits measured. As production per cow increased, the yearly dollar loss per cow declined from a high of $163 to $73 yearly in the group averaging 20,118 lb milk.; Dairy Day, 1988, Kansas State University, Manhattan, KS, 1988;
Keywords: Kansas Agricultural Experiment Station contribution; no. 89-107-S; Dairy; Reproductive traits; Holstein; Reproductive performance